Heterogeneous Light Conditions Reduce the Assimilate Translocation Towards Maize Ears - Guopeng Chen; Hong Chen; Kai Shi; Muhammad Ali Raza; George Bawa; Xin Sun; Tian Pu; Taiwen Yong; Weiguo Liu; Jiang Liu; Junbo Du; Feng Yang; et al. (Plants, 2020)
The border row crop in strip intercropped maize is often exposed to heterogeneous light conditions, resulting in increased photosynthesis and yield decreased. Previous studies have focused on photosynthetic productivity, whereas carbon allocation could also be one of the major causes of decreased yield. However, carbon distribution remains unclear in partially shaded conditions. In the present study, we applied heterogeneous light conditions (T), and one side of plants was shaded (T-30%), keeping the other side fully exposed to light (T-100%), as compared to control plants that were exposed entirely to full-light (CK). Dry weight, carbon assimilation, 13C abundance, and transport tissue structure were analyzed to clarify the carbon distribution in partial shading of plants. T caused a marked decline in dry weight and harvest index (HI), whereas dry weight in unshaded and shaded leaves did not differ. Net photosynthesis rate (Pn), the activity of sucrose phosphate synthase enzymes (SPS), and sucrose concentration increased in unshaded leaves. Appropriately, 5.7% of the 13C from unshaded leaves was transferred to shaded leaves. Furthermore, plasmodesma density in the unshaded (T-100%) and shaded (T-30%) leaves in T was not significantly different but was lower than that of CK. Similarly, the vascular bundle total area of T was decreased. 13C transfer from unshaded leaves to ear in T was decreased by 18.0% compared with that in CK. Moreover, 13C and sucrose concentration of stem in T were higher than those in CK. Our results suggested that, under heterogeneous light, shaded leaves as a sink imported the carbohydrates from the unshaded leaves. Ear and shaded leaf competed for carbohydrates, and were not conducive to tissue structure of sucrose transport, resulting in a decrease in the carbon proportion in the ear, harvest index, and ear weight.